2021
DOI: 10.1177/0309524x20984428
|View full text |Cite
|
Sign up to set email alerts
|

A new airfoil design method for wind turbine to improve maximum lift of airfoil

Abstract: A new wind turbine airfoil design method is established. This method generates an airfoil by fusing different airfoils. The airfoil designed by this method could restrict the airflow separation near the trailing edge of airfoil at high angle of attack, meanwhile the turbulence also is restricted. As a result, the maximum lift force is increased about 16.4% at high angle of attack. Meanwhile, the drag force is decreased about 31.3%. By analyzing the influence of scale factor and rotation angle on the airfoil ae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…For small scale wind turbine, researchers have primarily focused on developing new airfoil (Noronha & Krishna, 2021;Osei et al, 2020;Wang & Li, 2021), selecting an appropriate airfoil from the developed airfoil such as NACA and NREL series (Islam et al, 2019) to enhance the efficiency of wind turbines. For instance, Islam et al (Islam et al, 2019) presented a comparison study of different airfoils from the NACA and NREL airfoil families, aiming on suitability for small horizontal wind turbines, and finally showed that NACA airfoils have better average performance criteria whereas NREL airfoils have better stability criteria.…”
Section: Introductionmentioning
confidence: 99%
“…For small scale wind turbine, researchers have primarily focused on developing new airfoil (Noronha & Krishna, 2021;Osei et al, 2020;Wang & Li, 2021), selecting an appropriate airfoil from the developed airfoil such as NACA and NREL series (Islam et al, 2019) to enhance the efficiency of wind turbines. For instance, Islam et al (Islam et al, 2019) presented a comparison study of different airfoils from the NACA and NREL airfoil families, aiming on suitability for small horizontal wind turbines, and finally showed that NACA airfoils have better average performance criteria whereas NREL airfoils have better stability criteria.…”
Section: Introductionmentioning
confidence: 99%